The Effect of Variety and Methods of Extraction on The Yield and Content of Catechin of Gambir (Uncaria gambir Roxb) - Agus Sudibyo; Joseph J; Pardede -; Suprapto - (Balai Besar Industri Agro, 1988)
A research on the effect of varieties and methods of extraction to the yield and content of catechin of gambier has been conducted. Leaves of gambier from Uncaria gambir Roxb and Uncaria payakumbuh were extracted by steaming and boiling for 5-10 minutes, then pressed in 18.000 kg/cm^2 pressure and dried for 3-4 days. The yields of gambier were 6,44-6,47% (steaming) and 4,80-5,00% (boiling) respectively, whereas the catechin content of gambier were 64,45-65,08% (steaming) and 53,24-55,47% (boiling). Methods of extraction by steaming has a higher yield and catechin content than extraction by boiling.